PROBLEMATIKA KETERWAKILAN PEREMPUAN DI DPRD KOTA BANJARMASIN - Akhmad Rudini Akbar (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2014)
Akhmad Rudini Akbar, 2014. Problematic of Women Representation on Banjarmasin Parliament. Thesis, Program Study of Citizenship and Pancasila Education, Department of Education Social Sciences, Teacher and Education Science Faculty, University of Lambung Mangkurat. Counselor (I) Fatimah (II) Harpani Matnuh. Women Representation in parliament has been the focus of a lot of people since it is especially found on the election results that the percentage of women's representation in parliament does not reach the threshold of women representation. This study aims to see the women representation in Banjarmasin Parliament from the legislative election results. In addition, it also aims to know the problematic or the problems that occur in the women representation and the factors that affect the women representation in Banjarmasin Parliament.The method used in this study is qualitative data collection techniques by using the observation so that the researcher can see the problems of women representation in Banjarmasin Parliament, the interview is given to find out the problems directly from the informants as a source of data, and documentation is used to facilitate the researcher in collecting data both written documents or images as a data source.The research results show that the women representation is seen from the amount of Parliament members from among the women do not achieve the results of legislative elections but it nearly approaches the percentage of women representation. The problematic lead more to the limitation of women and the factors that influence it such as the difficulty of finding human resources who are courageous on the politic field and competent on it become a significant factor.In short, based on the results of this study, it is suggested that the women in Banjarmasin Parliament members should work optimally in order to further maximize their real work for the society, especially regarding to the issues of women's active role in efforts to increase the number women representation in the future and to strive for increasing the number of women representation to achieve the gender balance so that it can simplify the delivery of the interests and rights of women to go down to the community such as socializing or making events for instance seminars on increasing the women's representation. Keyword: Problematic, Women, Representation